The Perspectives of Women Professors on the Professoriate: A Missing Piece in the Narrative on Gender Equality in the University - Judith Harford (MDPI AG, 2018)
The under-representation of women in the professoriate is a widely acknowledged and complex phenomenon internationally. Ireland is no exception to this and indeed the issue of gender equality in Irish higher education has in the last 24 months emerged on the national policy agenda, largely as a result of a number of high profile legal cases and the subsequent setting up of an expert review panel (2015) and a gender equality taskforce (2017). What has now become clear internationally is that despite the advances women have made in terms of their participation rates as undergraduates, as well as the introduction of gender equity policies, the vast majority of professors in higher education institutions globally are men. Specifically, regarding Ireland in the period 2013-2015, even though 50% of the lecturer staff in universities were women, only 19% of professors were women. While the availability of such data is instructive, attention also needs to focus on examining the organizational culture and practices that appear to perpetuate such gender divisions and gendered patterns of action. On this, however, there is an almost complete absence of studies on the perspectives of women professors in Ireland on the professoriate. The study reported here, which was undertaken within the life story tradition, is one response to this deficit. It is based on interviews conducted with 21 women professors on their perspectives on working as professors in the university sphere in the period 2000‒2017. Four key themes were generated during the analysis of their testimony: they regarded universities as operating according to male-definitions of merit; they made a strategic choice not to engage in senior management roles (Senior management is defined as occupying the role of Dean level or above.); they considered there was no room for caring responsibilities in universities; and they emphasized the importance of validation, selection, and networks of support.